Hubungan penggunaan pornografi online terhadap perilaku seksual berisiko pada laki-laki yang belum menikah - Juayriah, Baiq; Hudaniah (Universitas Muhammadiyah Malang, 2026)
Online pornography use represents a form of media consumption involving sexual content that can influence how individuals perceive and express their sexual behavior. The increasing accessibility of online pornographic content among young men raises concerns about the escalation of risky sexual behaviors. This study aims to examine the relationship between online pornography use and risky sexual behavior among unmarried men. This research employed a quantitative correlational approach with a cross-sectional design, involving 387 male respondents aged 16–35 years. The instruments used were the Internet Pornography Questionnaire (IPQ) and the Sexual Risk Survey (SRS), and data were analyzed using the Spearman’s rho correlation test. The results showed a significant relationship between online pornography use and risky sexual behavior (ρ<0.05). These findings indicate that a higher level of acceptance toward pornography is associated with a greater tendency for individuals to engage in risky sexual behaviors. This study highlights the importance of sexual literacy and the enhancement of self-control as preventive efforts to mitigate the negative impacts of online pornography use among unmarried men.